The TRENDY multi-center randomized trial on hepatocellular carcinoma – Trial QA including automated treatment planning and benchmark-case results. Issue 3 (December 2017) - Habraken, Steven J.M.; Sharfo, Abdul Wahab M.; Buijsen, Jeroen; Verbakel, Wilko F.A.R.; Haasbeek, Cornelis J.A.; Öllers, Michel C.; Westerveld, Henrike; van Wieringen, Niek; Reerink, Onne; Seravalli, Enrica; Braam, Pètra M.; Wendling, Markus; et al.
Abstract: Background and purpose: The TRENDY trial is an international multi-center phase-II study, randomizing hepatocellular carcinoma (HCC) patients between transarterial chemoembolization (TACE) and stereotactic body radiation therapy (SBRT) with a target dose of 48–54 Gy in six fractions. The radiotherapy quality assurance (QA) program, including prospective plan feedback based on automated treatment planning, is described and results are reported. Materials and methods: Scans of a single patient were used as a benchmark case. Contours submitted by nine participating centers were compared with reference contours. The subsequent planning round was based on a single set of contours. A total of 20 plans from participating centers, including 12 from the benchmark case, 5 from a clinical pilot and 3 from the first study patients, were compared to automatically generated VMAT plans. Results: For the submitted liver contours, Dice Similarity Coefficients (DSC) with the reference delineation ranged from 0.925 to 0.954. For the GTV, the DSC varied between 0.721 and 0.876. For the 12 plans on the benchmark case, healthy liver normal-tissue complication probabilities (NTCPs) ranged from 0.2% to 22.2% with little correlation between NCTP and PTV-D95% ( R 2  < 0.3). Four protocol deviations were detected in the set of 20 treatment plans. Comparison with co-planar autoVMAT QA plans revealed these were due to too high target dose and suboptimal planning. Overall, autoVMAT resulted in an average liver NTCP reduction of 2.2 percent point (range: 16.2 percent point to −1.8 percent point, p  = 0.03), and lower doses to the healthy liver ( p  < 0.01) and gastrointestinal organs at risk ( p  < 0.001). Conclusions: Delineation variation resulted in feedback to participating centers. Automated treatment planning can play an important role in clinical trials for prospective plan QA as suboptimal plans were detected.